The extrajudicialization of procedures: a necessary path (Research, Society and Development, 2021)
As social conflicts change, becoming more complex, extrajudicialization emerges as an adequate means for pacifying such conflicts. This paper aims to analyze the phenomenon of extrajudicialization of conflicts, as well as its adequacy to the Brazilian legal framework, comparing it with other means of conflict resolution and demonstrating its positive points, as well as its disadvantages. For this, through a literature review, as well as data collected by official bodies and Brazilian legislation, it is sought to make a brief analysis of the Brazilian judicial system and the procedural reality after the 2015 Code of Civil Procedure and the need for adaptation of the means of conflict resolution in the search for social pacification, considering extrajudicialization as a form of resolution consistent with the current social reality. As a result, the importance of extrajudicialization of procedures was presented, within the field of effectiveness, efficiency and adequacy in the resolution of disputes, with the objective of reducing the number of cases in the Judiciary Branch, as well as promoting the swift resolution of conflicts, effective and adequate to your reality. On the other hand, the main obstacles to a wider use of extrajudicial procedures in the resolution of disputes were also presented.